Fas/FasL Pathway Participates in Regulation of Antiviral and Inflammatory Response during Mousepox Infection of Lungs - Karolina Bień; Justyna Sokołowska; Piotr Bąska; Zuzanna Nowak; Wanda Stankiewicz; Malgorzata Krzyzowska (Hindawi Limited, 2015)
Fas receptor-Fas ligand (FasL) signalling is involved in apoptosis of immune cells as well as of the virus infected target cells but increasing evidence accumulates on Fas as a mediator of apoptosis-independent processes such as induction of activating and proinflammatory signals. In this study, we examined the role of Fas/FasL pathway in inflammatory and antiviral response in lungs using a mousepox model applied to C57BL6/J, B6. MRL-Faslpr/J, and B6Smn.C3-Faslgld/J mice. Ectromelia virus (ECTV) infection of Fas- and FasL-deficient mice led to increased virus titers in lungs and decreased migration of IFN-γ expressing NK cells, CD4+ T cells, CD8+ T cells, and decreased IL-15 expression. The lungs of ECTV-infected Fas- and FasL-deficient mice showed significant inflammation during later phases of infection accompanied by decreased expression of anti-inflammatory IL-10 and TGF-β1 cytokines and disturbances in CXCL1 and CXCL9 expression. Experiments in vitro demonstrated that ECTV-infected cultures of epithelial cells, but not macrophages, upregulate Fas and FasL and are susceptible to Fas-induced apoptosis. Our study demonstrates that Fas/FasL pathway during ECTV infection of the lungs plays an important role in controlling local inflammatory response and mounting of antiviral response.